2007
DOI: 10.1111/j.1753-6405.2007.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of primary prevention services for cardiovascular disease in Australia's community pharmacies

Abstract: C ardiovascular diseases (CVD) remain the leading causes of m o r t a l i t y a n d m o r b i d i t y i n10 There has been little comparable national data of prevention services, including screening, offered by Australia's pharmacies. The aims of this study were to quantify the prevalence of community pharmacies that provided services for the primary prevention of CVD and to analyse pharmacy and pharmacist characteristics associated with these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…MM services related to disease management, such as diabetes, hypertension, asthma, anticoagulation and osteoporosis (referred by PCNZ as Level C and Level D services), were provided in less than 10% of respondent pharmacies. Similar results were found in studies in Australia, the USA and Europe, which also reported that pharmacists were routinely engaged in activities such as patient risk factor screening, but infrequently in the implementation of treatment or medication monitoring plans …”
Section: Discussionsupporting
confidence: 85%
“…MM services related to disease management, such as diabetes, hypertension, asthma, anticoagulation and osteoporosis (referred by PCNZ as Level C and Level D services), were provided in less than 10% of respondent pharmacies. Similar results were found in studies in Australia, the USA and Europe, which also reported that pharmacists were routinely engaged in activities such as patient risk factor screening, but infrequently in the implementation of treatment or medication monitoring plans …”
Section: Discussionsupporting
confidence: 85%
“…In this study, the number of respondents that had seen blood pressure monitoring services provided by any pharmacy they visited was low (27·5%), even though this type of screening has previously been found to the most commonly performed by pharmacists (9). This suggests that further promotion of professional CVD risk screening in pharmacies is warranted.…”
Section: Discussionmentioning
confidence: 62%
“…Research based on analyzing the primary prevention services available in Australia’s community pharmacies, found that blood pressure testing was the only screening test commonly in place (>50%) and cholesterol screening was much less frequent (9). It was reported that younger pharmacists were significantly more likely to have initiated blood pressure screening because of a broader education (9).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants were young with a B. Pharm. A study in Australian showed that younger pharmacists and pharmacies in regional shopping centers were associated with a higher level of preventive services for CVD [13]. This indicates that patient-focused services in community pharmacies can be applicable at any educational level after graduation following appropriate knowledge and training.…”
Section: Discussionmentioning
confidence: 99%